Artificial Intelligence and the Philosophy of Labour: Challenges and Prospects - Shimshek, H.A.; Kolegen, G.B. (NLC «Karaganda National Research University named after acad. Ye.A. Buketov», 2025)
The article offers a philosophical-ethical account of how labour is being transformed in the era of artificial intelligence. Drawing on classical conceptions of labour (Aristotle, Karl Marx, Hannah Arendt) and contemporary AI-ethics frameworks, it juxtaposes deontological constraints with utilitarian assessments of outcomes, thereby delineating the moral boundaries of permissible automation and the conditions of its legitimacy. A three tier model is proposed: conceptual foundations agency, dignity, and procedural justice; applied effects of technological unemployment and occupational redesign, algorithmic unfairness and the “responsibility gap”, alongside opportunities to reduce routine, enhance safety, and promote inclusion; operational requirements across the AI lifecycle explainability and traceability, Algorithmic Impact Assessment, the human-in-the-loop regime, post-market monitoring, as well as reskilling programmes and recognition of micro-credentials. It is shown that “fair automation” is achievable only when deontological red lines (rights, dignity, non-discrimination) are institutionalised and outcomes are optimised within these bounds. For the Kazakhstani context, a baseline governance package is proposed: transparent goal-setting, model and dataset “passports”, independent auditing, a right to human review of decisions, and infrastructure for just labour transitions.
Social philosophy - Әлеуметтік философия - Социальная философия
Keywords: artificial intelligence; philosophy of labour; deontology; utilitarianism; algorithmic fairness; explainability; responsibility gap; human-in-the-loop; Algorithmic Impact Assessment (AIA); reskilling